8 Bit Cmos Hybrid Digital-To-Analog Converter For Bluetooth Low Energy Application - Rosli, Alia (2019)
In the bluetooth low energy implementation, the digital-to-analog converters act as the bridge gap between digital signal processing chips, and power amplifiers that transmit analog signals. This thesis presents the design of a hybrid Digital-lo-Analog Converter( DAC) intended for RF transmitter in 2.45 GHz Bluetooth Low Energy (BLE) application by using CMOS 180 nm technology. The hybrid DAC design strategy is based on iterative scheme whose variables are adjusted in a simple way, minimizing the power consumption as well as area and also meeting the design specifications.